Lakuan maternal landak raya (Hystrix brachyura) didalam kurungan - Norsuhana A.H,; Shukor Md Nor,; Aminah A,; Zainal Zahari Z., (Universiti Kebangsaan Malaysia, 2009)
Maternal behaviour study of captive Malayan porcupines (Hystrix brachyura) was conducted within 2 months where six observation sessions were conducted, from Observation Sessions 1-6 (OS 1- OS 6). Observation session was carried out using continuous focal observation method. A single mother and new born Malayan porcupine was used as a sample. Identified maternal behaviors were resting, suckling, moving, licking newborn and eating. Time spent on resting and suckling was different (p<0.05) among OS 1- OS 6. In contrast, other activities such as moving, licking newborn and eating, were no different (p>0.05) significantly among observation sessions. The dominant behavior in first month observation (OS 1 - OS 3) was resting and followed by suckling. Different pattern was demonstrated in the second month (OS 4 - OS 6) where suckling by the newborn was found the highest and followed by resting. The mother has six teats located in the lateral thoracic (three in right lateral and three in left lateral). The observation showed that newborn porcupine preferred to use the front teats (T1 and T2) during suckling. Weaning time cannot be determined during the observation period, due to suckling behavior and time spent on suckling continued and increased.